The Effect of Increased Pork Hot Carcass Weights on Consumer Palatability Ratings of Top Loin Chops - E. A. Rice; A. B. Lerner; H. E. Price; J. C. Woodworth; M. D. Tokach; S. S. Dritz; R. D. Goodband; J. M. DeRouchey; M. W. Allerson; J. M. Gonzales; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate the effects of pork hot carcass weight on consumer palatability ratings of top loin chops. Pork loins (n = 200) were collected from 4 different hot carcass weight groups: light weight group (less than 246.5 lb; LT), medium-light weight group (246.5 to 262.5 lb; MLT), medium-heavy weight group (262.5 to 276.5 lb; MHVY), and a heavy weight group (276.5 lb and greater; HVY). Instrumental color, visual color and marbling, and pH were taken for each loin prior to fabrication. Loins from all weight groups differed (P<0.05) in weight (LTP>0.05) were found for loin instrumental color, subjective color, subjective marbling, purge loss, and pH. Carcass weight did not affect (P>0.05) juiciness, flavor, or overall like ratings, but did affect (P<0.05) tenderness ratings. Chops from the HVY group were rated as more (P<0.05) tender compared to chops from the LT weight group. Weight group did not contribute (P>0.05) to the percentage of chops rated acceptable for flavor and overall like. The greatest (P<0.05) percentage of samples were rated acceptable for juiciness for chops from the HVY weight group, and the lowest (P<0.05) percentage of acceptable ratings for tenderness for chops were from the LT weight group. Consumers perceived the lowest (P<0.05) percentage of chops from the HVY group as unsatisfactory quality in comparison to chops from the 2 lightest weight groups. Weight did not contribute (P>0.05) to consumer quality ratings. These results indicate top loin chops from heavier weight carcasses have improved tenderness compared to chops from lighter carcasses.
Keywords: consumer; heavy pigs; hot carcass weight; palatability; pork quality